Construction of target‐specific virus‐like particles for the delivery of algicidal compounds to harmful algae. (17th December 2014) - Kang, Beom Sik; Eom, Chi‐Yong; Kim, Wonduck; Kim, Pyoung il; Ju, Sun Yi; Ryu, Jaewon; Han, Gui Hwan; Oh, Jeong‐Il; Cho, Hoon; Baek, Seung Ho; Kim, Gueeda; Kim, Minju; et al.
Summary Harmful algal blooms (HABs) can lead to substantial socio‐economic losses and extensive damage to aquatic ecosystems, drinking water sources and human health. Common algicidal techniques, including ozonation, ultrasonic treatment and dispersion of algae‐killing chemicals, are unsatisfactory both economically and ecologically. This study therefore presents a novel alternative strategy for the efficient control of deleterious algae via the use of host‐specific virus‐like particles (VLPs) combined with chemically synthesized algicidal compounds. The capsid protein of HcRNAV34, a single‐stranded RNA virus that infects the toxic dinoflagellate, Heterocapsa circularisquama, was expressed in and purified from Escherichia coli and then self‐assembled into VLPs in vitro. Next, the algicidal compound, thiazolidinedione 49 (TD49), was encapsidated into HcRNAV34 VLPs for specific delivery to H. circularisquama. Consequently, HcRNAV34 VLPs demonstrated the same host selectivity as naturally occurring HcRNAV34 virions, while TD49‐encapsidated VLPs showed a more potent target‐specific algicidal effect than TD49 alone. These results indicate that target‐specific VLPs for the delivery of cytotoxic compounds to nuisance algae might provide a safe, environmentally friendly approach for the management of HABs in aquatic ecosystems.